(m-CF3-PhSe)2 benefits against anxiety-like phenotype associated with synaptic plasticity impairment and NMDAR-mediated neurotoxicity in young mice exposed to a lifestyle model. (1st June 2023) - Müller, Sabrina G.; Jardim, Natália S.; Lutz, Guilherme; Zeni, Gilson; Nogueira, Cristina W.
Abstract: Lifestyle habits including energy-dense foods and ethanol intake are associated with anxiety disorders. m -Trifluoromethyl-diphenyl diselenide [( m -CF3 -PhSe)2 ] has been reported to modulate serotonergic and opioidergic systems and elicit an anxiolytic-like phenotype in animal models. This study investigated if the modulation of synaptic plasticity and NMDAR-mediated neurotoxicity contributes to the ( m -CF3 -PhSe)2 anxiolytic-like effect in young mice exposed to a lifestyle model. Swiss male mice (25-days old) were subjected to a lifestyle model, an energy-dense diet (20:20% lard: corn syrup) from the postnatal day (PND) 25–66 and sporadic ethanol (2 g/kg) (3 x a week, intragastrically, i.g.) from PND 45 to 60. From PND 60 to 66, mice received ( m -CF3 -PhSe)2 (5 mg/kg/day; i.g). The corresponding vehicle (control) groups were carried out. After, mice performed anxiety-like behavioral tests. Mice exposed only to an energy-dense diet or sporadic ethanol did not show an anxiety-like phenotype. ( m -CF3 -PhSe)2 abolished the anxiety-like phenotype in young mice exposed to a lifestyle model. Anxious-like mice showed increased levels of cerebral cortical NMDAR2A and 2B, NLRP3 and inflammatory markers, and decreased contents of synaptophysin, PSD95, and TRκB/BDNF/CREB signaling. ( m -CF3 -PhSe)2 reversed cerebral cortical neurotoxicity, the increased levels of NMDA2A and 2B, and decreased levels of synaptic plasticity-related signaling in the cerebral cortex of young mice exposed to a lifestyle model. In conclusion, the ( m -CF3 -PhSe)2 anxiolytic-like effect was associated with the modulation of NMDAR-mediated neurotoxicity and synaptic plasticity in the cerebral cortex of young mice exposed to the lifestyle model. Graphical abstract: Image 1 Highlights: A lifestyle model induces anxiety-like phenotype in young mice. ( m -CF3-PhSe)2 abolishes the anxiety-like phenotype in young mice. ( m -CF3-PhSe)2 counteracts NDMAR-mediated neurotoxicity in anxious mice. Synaptic plasticity improvement contributes to the ( m -CF3-PhSe)2 anxiolytic-like effects. Anti-inflammatory properties are related to ( m -CF3-PhSe)2 beneficial effects.